Transforming growth factor beta stimulates collagen-matrix contraction by fibroblasts: implications for wound healing. - Montesano, R (1988)
An important event during wound healing is the contraction of newly formed connective tissue (granulation tissue) by fibroblasts. The role of polypeptide growth factors in the process of wound contraction was investigated by analyzing the influence of transforming growth factor beta (TGF-beta), platelet-derived growth factor on the ability of fibroblasts to contract a collagen matrix in an in vitro system. TGF-beta, but not the other growth factors tested, markedly enhanced the ability of BHK-21,3T3-L1, and human foreskin fibroblasts to contract collagen gels. These results suggest that TGF-beta released from platelets and inflammatory cells at sites of tissue injury stimulates fibroblasts to contract the provisional wound matrix and that this effect contributes to the ability of TGF-beta to accelerate wound healing.